Impact of Twice-Weekly Islamic Fasting on Cardiovascular Risk Factors in Women with Type 2 Diabetes Mellitus - Afandi, Bachar; kaabi, Juma Al; Sharma, Charu (Journal of Diabetes and Endocrine Practice, 2025)
Twice-Weekly Islamic Fasting is a unique form of intermittent fasting observed by Muslims on Mondays and Thursdays. While Ramadan and other forms of intermittent fasting have been extensively studied, limited data exist on the clinical impact of Twice-Weekly Islamic Fasting among patients with type 2 diabetes mellitus (T2DM).This study aimed to determine the prevalence and impact of Twice-Weekly Islamic Fasting on cardiovascular risk factors among Emirati women with T2DM.One hundred Muslim women from the outpatient diabetes clinic at Tawam Hospital, Al Ain, United Arab Emirates, were interviewed face-to-face using a structured questionnaire. Based on their reported observation of Twice Weekly Islamic Fasting practices, participants were categorized into two groups: group 1 (n = 37, 37%) were patients who observe this fasting pattern regularly and group 2 (n = 63, 63%) included patients who do not. Medical records were reviewed for weight, type and duration of diabetes, body mass index (BMI), type of treatment, blood pressure (BP), glycated hemoglobin (HbA1c), and lipid panel.Among 100 participants, 37% reported observing Twice-Weekly Islamic Fasting regularly. Fasting individuals were older (mean age 62 vs. 56 years, p < 0.05) and with longer duration of diabetes (22 vs. 19 years, p < 0.05) compared with nonfasting participants. The fasting group showed better glycemic control, with a lower mean HbA1c (7.59 ± 2.1% vs. 8.07 ± 2.0%, p = 0.077), although the difference was not statistically significant. While BMI, lipid profiles, and BP did not show any statistically significant differences, fasting participants exhibited a slightly lower systolic BP (128 ± 15.7 vs. 132.9 ± 16.4 mm Hg) and a slight improvement in total cholesterol/high-density lipoprotein ratio in participants with a diabetes duration exceeding 10 years.This pilot study found that 37% of Emirati women with T2DM practice Twice-Weekly Islamic Fasting. While statistical significance was not reached, trends suggest potential benefits for glycemic control and weight. Given the widespread observance of this practice, health care providers play a crucial role in guiding patients who choose to fast, ensuring a balance between traditional practices and safe diabetes management. Future research should investigate the long-term impact of Twice-Weekly Islamic Fasting on metabolic and cardiovascular health.
Keywords: diabetes; fasting; religion; cardiovascular; women; intermittent fasting